Accuracy, inter-observer and intra-observer reliability in topography assessment of multifocal contact lens centration. Issue 5 (October 2020) - Zeri, Fabrizio; Di Vizio, Assunta; Guida, Maurizio; Rotondi, Anastasia; Tavazzi, Silvia; Naroo, Shehzad A.
Abstract: Purpose: To evaluate the accuracy and reliability (inter and intra-observer) of a method to assess multifocal contact lenses (MCLs) centration using a corneal topography unit. Method: Daily-disposable MCLs (Fusion 1 day Presbyo) were fitted on both eyes of the subjects. For each lens fit a slit lamp digital picture and videokeratograph image were taken in a rapid but randomised sequence. Photo-editing software was used to assess the position of the MCL centre with respect to pupil centre as taken from the slit lamp photograph. The position of the MCL centre was automatically detected as the point of maximum curvature from the videokeratography. Three further manual and qualitative procedures to detect MCL centre, comparing a template of CLs optic zones to the videokeratographic image were performed by 4 practitioners using 3 different algorithms to represent the topographic map. Each manual reading was repeated 3 times. Results: Twenty-two subjects (11 males) aged 22.8 ± 1.9 years (range 20.8–27.0 years) were recruited. The accuracy of the 4 topographic assessments in determining the centre coordinates of the MCL with respect to SL assessment was good: no differences were found in the left eyes and although in the right eyes a more temporal and superior position of MCLs was determined (paired t -test, p < 0.05) the difference was clinically negligible (0.16 ± 0.36 mm horizontally, 0.23 ± 0.48 vertically). Amongst the 4 practitioners one-way Anova for repeated measures showed no differences for any of the 3 manual assessments. Intra-class correlation coefficient was calculated among the 3 readings for each manual procedure and was very good (between 0.75 and 0.98) in 3 practitioners and moderate (between 0.49 and 0.92) in the fourth. Conclusions: The assessment of MCL centration by performing corneal topography over the MCL is an accurate method. Furthermore, inter and intra-practitioner reliability showed by manual procedures appeared very good.